2015
DOI: 10.1007/s00586-015-3889-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TLICS for thoracolumbar fractures

Abstract: The study's results demonstrate that conservative treatment for TLICS 4 thoracolumbar fractures can be safely applied. The conservative treatment of cases scoring TLICS 4 is equally effective to those scoring ≤3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Hence, with relative frequencies being analyzed relative to the total number of participants, the sum of relative frequencies could exceed 100 %. Descriptive statistics and the Fisher exact test (significance level a = 0.05) were used to analyze any differences between the five world regions, and the influence of clinical experience (B10, [11][12][13][14][15][16][17][18][19][20] or [20 years). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, with relative frequencies being analyzed relative to the total number of participants, the sum of relative frequencies could exceed 100 %. Descriptive statistics and the Fisher exact test (significance level a = 0.05) were used to analyze any differences between the five world regions, and the influence of clinical experience (B10, [11][12][13][14][15][16][17][18][19][20] or [20 years). …”
Section: Discussionmentioning
confidence: 99%
“…Clinical parameters may include patients' neurological status as a critical indicator, and injury morphology [6][7][8][9]. Also radiographic measurements are crucial, including sagittal alignment (kyphosis) and the amount of vertebral body height loss (VBHL) [10][11][12]. Changes in the kyphotic angle may indicate the degree of instability of the injured spinal segment and progression of deformity.…”
Section: Introductionmentioning
confidence: 99%
“…For Kyphotic angle:p value at admission was 0.06 and become 0.37 at follow up . Spiros G. Pneumaticos et al (8) 2016 in a study for evaluation TLICS for thoracolumbar fractures, results for patients whose TLICS score 4, the different parameters were : Difference shown due to decreased number of cases managed conservatively in the study.Our cases were treated and classifiedaccording to the TLICS. Thoracolumbar injuries scoring4 were treated conservatively.…”
Section: Discussionmentioning
confidence: 92%
“…However, with a score of less than five points, many authors criticized the TLICS because some of these injuries that were treated non-surgically may develop further deformity (generally kyphosis) or severe pain/disability (8)(9)(10). In this context, considering a historical review, many radiological features were suggested for an unfavorable outcome with non surgical treatment for burst fractures, even though they are based on low level of evidence/poor quality studies.…”
mentioning
confidence: 99%
“…Magnetic resonance imaging may show signs of severe injuries that would be underestimated in some cases using plain radiographs or CT scan. However, MRI changes must be interpreted together with CT scan, once its use isolated may lead to unnecessary surgeries (1,4,9,14,17,19).…”
mentioning
confidence: 99%